2019
DOI: 10.1017/s1751731118001714
|View full text |Cite
|
Sign up to set email alerts
|

A genome scan for selection signatures in Taihu pig breeds using next-generation sequencing

Abstract: Taihu pig breeds are the most prolific breeds of swine in the world, and they also have superior economic traits, including high resistance to disease, superior meat quality, high resistance to crude feed and a docile temperament. The formation of these phenotypic characteristics is largely a result of long-term artificial or natural selection. Therefore, exploring selection signatures in the genomes of the Taihu pigs will help us to identify porcine genes related to productivity traits, disease and behaviour.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Other studies that involved a few Asian and European pig breeds investigated signatures of selection in the porcine genome using SNP chip or partial/reduced or wholegenome re-sequencing datasets and highlighted loci of economic importance [7,[31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that involved a few Asian and European pig breeds investigated signatures of selection in the porcine genome using SNP chip or partial/reduced or wholegenome re-sequencing datasets and highlighted loci of economic importance [7,[31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…These breeds represent genetic resources adapted to local agro-climatic and environmental conditions. To date, the genome architecture of CNVs has been studied mainly in Asian autochthonous populations/ breeds (Li et al 2012;Wang et al 2014Wang et al , 2015bWang et al , 2019bJiang et al 2014;Dong et al 2015;Xie et al 2016). European autochthonous pig breeds have been mainly investigated by exploring their genetic variability using SNP data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the genes under selection to be overrepresented in pathways related to lipids (e.g., alpha-Linolenic acid metabolism, Corrected p = 0.005; Linoleic acid metabolism, Corrected p = 0.02; Arachidonic acid metabolism, Corrected p = 0.05; ether lipid metabolism, p < 0.05), which were reported to be relevant to lipogenesis in Taihu pigs [32]. This finding indicated that the genes related to lipids traits have experienced intensive selection, and might be correlated with the fat tail trait of Aldabas and Kurdyuchnyj sheep in this study.…”
Section: Discussionmentioning
confidence: 69%